Sosialisasi Bahaya Narkoba dan Kenakalan Remaja - Arpin, Syaiful (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This Community Service Program (KKN) was conducted at SMAN 1 POLO-POLIA, focusing on preventive measures against the dangers of drugs and juvenile delinquency. The high rate of juvenile delinquency, including drug abuse, poses a serious threat to the younger generation and the future of the nation. The goal of this outreach program is to increase understanding, awareness, and healthy decision-making skills in adolescents, supported by a framework of contemporary psychological and sociological theories. The methods used are interactive counseling, group discussions, and the distribution of educational materials. The expected outcome is a change in adolescents' perceptions and positive attitudes toward the importance of avoiding drugs and deviant behavior, as well as strengthening the role of the family and community as a support system.